Modeling of higher order systems using artificial bee colony algorithm - Aytekin Bağış; Halit Senberber (An International Journal of Optimization and Control: Theories & Applications, 2016)
In this work, modeling of the higher order systems based on the use of the artificial bee colony (ABC) algorithm were examined. Proposed model parameters for the sample systems in the literature were obtained by using the algorithm, and its performance was presented comparatively with the other methods. Simulation results show that the ABC algorithm based system modeling approach can be used as an efficient and powerful method for higher order systems.